An Analysis of Translation Shifts in Indonesian - English Film Subtitles: A Study of Comic 8 - A.A.I. Mas Trisnamayuni (CV Wahana Publikasi, 2026)
This study aims to analyze translation shifts and language style in the Indonesian - English subtitles of the film Comic 8. The research focuses on identifying the types of translation shifts and examining how language style influences the translation process in an audiovisual context. A descriptive qualitative method was employed, using Catford’s theory of translation shifts as the main analytical framework. The data consist of selected subtitle excerpts that represent the shifts occurring between the source language (Indonesian) and the target language (English). The findings indicate that unit shift is the most dominant type of translation shift identified in the data. Most shifts involve changes in rank, particularly from clauses or phrases in the source language into sentences in the target language. These shifts are influenced by structural differences between Indonesian and English, as well as the need to achieve clarity, naturalness, and acceptability in the target language. In addition, unit shifts are also found to occur from higher to lower ranks, demonstrating that shifts are flexible and context-dependent. Category shift is identified in only one case, involving both structure shift and class shift, which function to produce more appropriate and natural expressions in the target language. In terms of language style, the results show that casual style is predominantly used, reflecting the informal nature of film dialogue. The translator tends to maintain this style to preserve the communicative tone and social meaning of the original text. In conclusion, translation shifts, particularly unit shifts, play a crucial role in ensuring effective subtitle translation, while language style contributes to maintaining the naturalness and communicative function of the translated text.